Happy Birthday: Form and Function of Language - Oktiva Herry Chandra (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
This article tells about the structure of greeting discourse, how people think about it and its function in social interaction.One of language functions is to tighten solidarity among members of a community. This can be done by using some expressions that show a positive intention of speaker to hearer. Saying congratulation to someone who has this special moment, such as birthday celebration, is one way to realize this function. When doing so, s/he is not only expressing her/his true feeling. Behind it, that expression represents diverse perception and value owned by people who produce and inteprete them. The data were collected form the conversationcontained in WA mobile application. They are taken from two groups, namely Semarak Juring and Dosen dan Tendik. The method of non-participatory participation was used and was followed by note taking technique. The result shows that the different representation of birthday greeting indicates various social relation between addresseer and addressee. This representation also marks differentfunctions of birthday greetings Keywords: form,function, social function, sympathy and respect .